Pengaruh Media Sosial Terhadap Proses Pengambilan Keputusan Pembelian Online Konsumen Pada Masa Pandemi COVID-19 - Ma’mun Sutisna; Julia Siti Afnia Putri; Ira Siti Sarah (Forum Kerjasama Pendidikan Tinggi, 2023)
Online shopping transactions in Indonesia have increased along with the increasing of internet and social media users. Brands start to use social media as a marketing which made consumers look for information on a product or when buying through it. Consumers love online shopping more as many benefits they get, especially during the COVID-19 which keeps people at home. The research aim is to look at how social media influences online decision-making process. Data were obtained by means of a questionnaire to 168 social media users and had made online purchases during the COVID-19. Samples were taken using purposive sampling technique. Data were analyzed using simple linear regression. The results of the research analysis showed that social media had a positive and influential impact on each stage of online purchases decision-making. The social media dimension in this study is able to explain online purchases decision-making process by 59.4%. is a short summary of the paper to help the reader quickly ascertain the purpose of the study and match the research needs. The abstract must be clear and informative, provide a statement for the problem, the method of solving the problem, and the conclusions/provisional results of your research. Abstract between 90 and 230 words in length. Avoid unusual abbreviations and define all symbols used in the abstract. Using keywords related to the research topic is recommended.